Minerals Beneficiation - Pebble Milling Practice at the South African Gold Mines of Union Corp. Ltd - O. A. E. Jackson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1960)
Pebble milling has been practiced in the reduction works of South Africa gold mines for well over 50 years. Originally flint pebbles were imported from Denmark to grind stamp-mill amalgamation-process tailing, which contained a good deal of extractable gold, but local operators soon found that large pieces of ore could be used for the same purpose. The ore is a hard, tough conglomerate in which quartz pebbles are cemented together by a matrix of redeposited silica interspersed with pyrite crystals. The gold, rarely visible, occurs as fine particles mostly segregated at the interface of the pebble and matrix, although a small fraction occurs within the pyrite crystals. There is seldom any gold in the pebbles themselves. Following the usual South African practice in pebble milling, Union Corp. grinds the ore wet in two or three milling stages incorporating classification. The sized broken ore used as grinding media is separated from the main ore stream in the crushing section that prepares the ore for milling. Where the ore channel, or reef, is narrow there is a shortage of large pebbles. In this case primary grinding may be done in ball mills or, more recently, in rod mills, which cost less per ton to operate. The trend, however, is to prepare finer feed for the milling section. This makes it possible to use smaller primary pebbles and eliminates the need for steel. REDUCTION WORKS OF UNION CORP. LTD. Union Corp. Ltd. exercises financial and technical control over a group of seven gold mines in the Transvaal and Orange Free State. In the Transvaal, with one exception. the mines lie 20 to 40 miles east of Johannesburg, in flat or gently rolling countryside. Winkelhaak, the first of several new mines that will be developed by Union Corp., is located in similar terrain in an entirely new gold mining district about 80 miles east of Johannesburg. Table I gives details of milling units for six of the Union Corp. mines, together with the tonnage milled in 1957. Winkelhaak Mines Ltd. is not included, as it did not begin milling until 1958. This reduction plant has no crushing section; ore is ground directly from the mine (autogenously) in 12x16-ft mills. Because these operations are still in development, they are not described in this article. It will be noted that certain reduction works have mills of more than one size in the same milling stage. This came about when plant extensions in- corporated larger units. In the case of Geduld Propty. Mines Ltd., which began milling operations 50 years ago, the primary stage is stamp milling. The reduction works follow a uniform pattern and are usually joined to the main ore shaft. Ore from other shafts is brought by standard-gage railway and dumped into a common transfer bin. The trend is to increase surface storage capacity to enable the crushing and milling sections to operate at a steady rate, independent of fluctuating ore deliveries from mine. Milling and cyanide extraction divisions of new mines are always designed to allow for extensions as mine production increases. The conveying, washing, and screening system of the crushing section is usually laid out in final form, with additional space for more crushing equipment. The crushing sections operate on one shift during early years of mine production; a second shift is introduced when the mining rate warrants it. Ample surge capacity is provided. Crushing and milling is done only on weekdays, as the law does not allow these operations to take place on Sunday in any plants constructed since 1911. The cyanide extraction sections, however, operate continuously seven days a week, drawing on mill pulp gradually built up in the thickeners during the week. Construction and equipment of milling plants follow standard practice. Dilution water is drawn from a large, high-level tank to obtain constant pressure, but gland service water for the pulp pumps is reticulated from high-pressure, two-stage pumps. The mills are equipped with the most up-to-date machinery and are designed to save labor. They compare favorably with milling plants in countries where native labor does not exist, and automatic controls are being installed wherever feasible. Hydrocyclone classifiers have replaced mechanical classifiers in modern milling plants, chiefly because of the saving in capital outlay, maintenance, and building space. The hydroclones are fed from steady head boxes rather than directly from pumps, and dilution water is introduced into these boxes. Tests have shown that in steadiness of operation and separating efficiency cyclones are comparable to mechanical classifiers. but protective stationarv screens are needed to keep the spigots clear. Rubber-lined pumps are used for pulp of about 3 mesh or finer and metal-lined pumps for coarser material. None of the Union Corp. milling plants practices gravity concentration of coarse gold by amalgamation or the use of corduroy blankets. Studies have proved that no economic case can be made for these methods, which complicate the milling process and demand extra precautions against theft.